Chapter 2 Governance of Artificial Intelligence Emerging international trends and policy frames - Ulnicane, Inga (Taylor & Francis, 2022)
This chapter aims to contribute to AI research by providing insights into policy dynamics and content. Using concepts and insights from social studies of emerging sciences and technologies such as performative function of hypes and expectations as well as collaboration and competition dynamics in emerging fields helps to make sense of emerging AI policies, politics and governance, to contextualise recent AI policies and governance in a longer-term development of emerging technologies and to critically reflect on them.